Bilingual students, language conflict, language - culture shock: Situations faced by teachers assigned to eastern regions of Turkey - Kızıltaş, Yusuf (Afyon Kocatepe Üniversitesi)
Many bilingual students studying at schools in rural areas of Eastern and Southeastern Turkey experience language conflict in the process of acquiring Turkish. Likewise, teachers appointed to schools where bilingual students are educated, especially from the western regions of Turkey, have problems adapting to the region’s culture and language. The problems experienced and seen cause language and culture shock for teachers. At the same time, these problems lead to various negativities on students and teachers in the education process. In this study, language conflict experienced by bilingual students was evaluated according to teacher opinions. Likewise, it is aimed to question the dimensions and consequences of language and culture shock in teachers. Teachers from different branches (n=120) working in the district villages of Van province were included in the study group. Research data were collected via an online questionnaire in the spring semester of the 2020-2021 academic year. The collected data were analyzed with the MaxQDA 2020 program. It was concluded that the students experienced intense language conflict at school. Similarly, it was concluded that the teachers also experienced language and culture shocks in the eastern regions where they were assigned.

Türkiye’nin Doğu ve Güneydoğusunun kırsal bölgelerinde bulunan okullarda eğitim alan birçok iki dilli öğrenciler Türkçeyi edinme sürecinde dil çatışması yaşamaktadırlar. Aynı şekilde iki dilli öğrencilerin eğitim gördüğü okullara Türkiye’nin özellikle batı bölgelerinden atanan öğretmenler de bölgenin kültürüne ve diline uyum sağlamada sorun yaşamaktadırlar. Yaşanan ve görülen sorunlar öğretmenler için dil ve kültür şokuna neden olmaktadır. Aynı zamanda bu sorunlar, eğitim sürecinde öğrenci ve öğretmenler üzerinde çeşitli olumsuzluklara yol açmaktadır. Bu çalışmada iki dilli öğrencilerde yaşanan dil çatışması öğretmen görüşlerine göre değerlendirilmiştir. Aynı şekilde, öğretmenlerde de dil ve kültür şokunun boyutlarını, sonuçlarını sorgulamak amaçlanmıştır. Van ilçe köylerinde görev yapan farklı branşlardan öğretmenler (n=120) çalışma grubuna dâhil edilmiştir. Araştırma verileri 2020-2021 eğitim-öğretim yılı bahar döneminde çevrimiçi anket yoluyla toplanmıştır. Toplanan veriler MaxQDA 2020 programı ile analiz edilmiştir. Öğrencilerin okulda yoğun dil çatışması yaşadıkları sonucu ortaya çıkmıştır. Benzer şekilde öğretmenlerin de atandıkları doğu bölgelerinde dil ve kültür şokları yaşadıkları sonucuna varılmıştır.
İki dilli öğrenciler, dil çatışması, dil - kültür şoku: Türkiye’nin doğu bölgelerine atanan öğretmenlerin yüzleştikleri durumlar
Keywords: Bilingual Students; Language Conflict; Language Shock; Culture Shock; Teachers; İki Dilli Öğrenciler; Dil Çatışması; Dil Şoku; Kültür Şoku; Öğretmenler